State Awards - Grigoryeva, Elena; Kaftanov, Andrei (project baikal, 2017)
In the beginning of 2017 our colleagues and authors of Project Baikal received several state awards. Andrei Kaftanov received the Russian Federation Presidential Certificate of Honour for his active international and scientific work. Andrei introduced to PB the Swiss journalist Guy Mettan, who later became president of the Geneva Parliament. His valuable article on the Geneva-Lausanne agglomeration was published in PB 9. Guy Mettan was awarded the Order of Friendship. Andrei Bokov, who has also greatly contributed to PB (PB 5, PB 26, PB 50 and PB 51), was awarded the honorary title National Architect of the RF.
Keywords: honorary title National Architect of the RF; the Russian Federation Presidential Certificate of Honour; Order of Friendship